Performing and observing complex skills in gymnastics: An investigation of prototypical movement patterns and perceptual-cognitive processes - Mack, M. (Universität Leipzig, 2021)
In gymnastics, the performance is evaluated by a subjective rating (Plessner & Haar, 2006), whereby one of the biggest problems is the validity and reliability of judgment (Lesko?sek et al., 2010; Pajek et al., 2013). The process of observing and evaluating complex motor skills such as those found in gymnastics is located in the cyclical inter action between perception and action (Dosseville et al., 2014; Prinz, 1997), raising the key question, how the quantifiable movement execution is related to the perceived move ment quality. Therefore, the thesis aimed at a first step to kinematically analyze selected prototypical gymnastics skills to investigate at a second step the underlying perceptual cognitive mechanism when observing and evaluating those skills. In the analysis of kinematics, it was focused on the classification and structuring of temporal-spatial con tinuous kinematic movement patterns and their relationship to the perceived movement quality. In the investigation of the perceptual-cognitive mechanism, it was focused on how skill kinematics are related to the perceived movement quality. Furthermore was the gaze pattern evaluated and examined during the observation. Five consecutive studies were conducted to achieve those objectives. It was shown that complex gymnastics skills can be kinematically structured into proto typical movement patterns, which differ concerning certain variant and invariant kine matic characteristics. The results of a model-based approach to predict perceived move ment quality out of the kinematics of gymnastics skills showed a significant relationship between the predicted score and the true score. Overall, the models worked best for the vault skill, which was the shortest skill with the least spatial variability. Out of all models, the neural network approach showed the best results. Furthermore, it was found, that the similarity of the kinematics of gymnastics skills did not correlate with the similarity of the perceived movement quality. During the evaluation, the gaze pattern was influenced by the manipulation of the amount of non-kinematic information. This was especially the case for the last skill. Expertise seemingly influenced the perceptual cognitive mechanism partially, but no clear pattern was visible. The results provided first insights on how gymnastics performances and the resulting judgment scores are related. The complexity of gymnastics skills and additionally, the similarity of the performance level in high elite sport is increasing. This challenge as well as the fast development of technologies leads to the occurrence of computer-based judging systems. Their reliability and validity, but also their challenges and opportunities in artistic gymnastics should be further investigated.